Green Marketing Strategy in Efforts to Preserve the Environment - Devi Noviyanti (UIN Antasari Banjarmasin, 2021)
Various natural damage on land, sea, and air has shown that humans as creatures who have a mind should think of solutions and make various improvements to save nature and the environment. Marketing that has created products through the production process has a significant role in saving nature and the environment. The green marketing strategy tries to provide an alternative for companies to participate in efforts to preserve and save the environment from damage. This strategy is expected to help companies meet society's demands and consumers who want products that are not harmful to their health and the environment. In addition, this strategy is also expected to bring companies to fulfill their social responsibilities by government regulations